2016
DOI: 10.1159/000443219
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Intraoperative Blood Loss on Long-Term Outcomes after Curative Gastrectomy of Patients with Stage II/III Gastric Cancer

Abstract: Background/Aims: Gastrectomy with systemic lymphadenectomy sometimes causes excessive bleeding even by experienced surgeons. The aim of this study was to evaluate how intraoperative estimated blood loss (EBL) affected the long-term outcomes after curative surgery of patients with stage II/III gastric cancer (GC). Methods: This study included 203 patients with stage II/III GC who did not receive perioperative blood transfusion between 1999 and 2015. The optimal cutoff and the prognostic significance of EBL were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…To our knowledge, the present study was the first to demonstrate the influence of EIBL on the risk of PCCs and length of stay following VATS lobectomy for operable NSCLC. Because the receipt of perioperative blood transfusion could exert the immunosuppressive effects and then worsen the surgical outcomes, we only included the patients who did not receive any perioperative blood transfusion to avoid potential confounding bias risks influencing the actual value of EIBL, as many investigators previously suggested [ 11 , 13 ]. In our series, a ROC analysis was employed to determine a threshold value of EIBL that had the discriminatory ability for the prediction of PCCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, the present study was the first to demonstrate the influence of EIBL on the risk of PCCs and length of stay following VATS lobectomy for operable NSCLC. Because the receipt of perioperative blood transfusion could exert the immunosuppressive effects and then worsen the surgical outcomes, we only included the patients who did not receive any perioperative blood transfusion to avoid potential confounding bias risks influencing the actual value of EIBL, as many investigators previously suggested [ 11 , 13 ]. In our series, a ROC analysis was employed to determine a threshold value of EIBL that had the discriminatory ability for the prediction of PCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, evidence indicates that a larger volume of EIBL has the ability to directly cause the immune dysfunction and impair the nutritional status because of a significant loss of plasma constituents and leukocytes that engage in the anticancer immunity [ 13 ]. Angele et al [ 29 ] reviewed current experimental studies utilizing the models of trauma and hemorrhagic shock, which have defined the effects on the immune-inflammatory responses, and found that blood loss and surgical injury can suppress the cell-mediated immune responses through the depression of mitogenic response of T-lymphocytes, macrophage antigen presentation capacity and amounts of T-helper 1 lymphokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Han and co‐workers reported that free cancer cells can be released intraperitoneally by improper handling of lymphovascular vessels of the stomach. In addition, some studies have reported that the amount of IBL was associated with tumour recurrence and poor outcome. Arita et al .…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative blood loss has been shown to be associated with prognosis of patients in gastric cancer. 39 , 40 Kamei et al reported that curative resection with lower blood loss can contribute to improved survival. 41 Moreover, the less intraoperative blood loss may promote postoperative recovery, especially for elderly patients.…”
Section: Discussionmentioning
confidence: 99%